A Competent Automatic Test Packet Generation and Fault Lo-calization for Network Model - Kumar, Bura Vijay; Yamsani, Nagendar; Aluvala, Srinivas; Naik, Dr. K. Seena (International Journal of Engineering and Technology, 2018)
The developing of the fault locating in the network brought about tremendous changes for business models, industry, science and technology applications. The implementation of Automatic test Packet Generation (ATPG) in the network tests for faultiness in the network. It test for liveliness in the network at runtime with the aid of test packets by suitable rules namely forwarding, drop and congestion and fix the problem in the network so that one can easily locate the link failure at each and every terminal in the network in less time. The simulations are carried out with the help of jdk tool to evaluate the port failures in all cases of the rule. The results shows the efficient performance in case of fault localization algorithm that outperforms other traditional approaches.